Improving Students' Speaking Skill Through Role Play - Indah Tri Wibawanti (Language-Edu, 2020)
AbstractSome of Elementary students had low achievement in English at speaking ability. They didn’t have strong motivation in studying English, they were afraid to speak English. Therefore, a special method is needed to improve the students‘ speaking ability. The research design of this study was a classroom action research. The subjects of the research were 30 students of the theater students. This study was done in two cycles. However before implementing these cycles, the researcher carried out preliminary study to find out the students’ problem in studying English. This study was aimed to improve the students’ speaking ability by implementing a role play technique. To measure their improvements in speaking ability, the researcher has determined the criteria of success. And the student was said successful if student got a least 70. The class percentage was said successful if 85% the students or more reached the passing grade. The researcher employed the collaborative classroom action research design and the researcher was assisted by a collaborator teacher in conducting the study. The research was conducted in four main steps; Planning of action, observation, implementation and reflection. The implementation of role play made students more motivated in joining the speaking class. They paid more attention on the lesson. The procedures in implementing role play are: The teacher gave leading question and motivation to the students, the teacher gave special vocabulary and some expressions related with role play, gave special technique how to memorize vocabularies, organized the group of the students, provided the situation and dialogue to be role played, asked the students to practice the role plays and asked group the students to perform the role play in front of the class. The result of the study reveals that role play can improve the speaking ability. The implementation of role play made students more motivated in joining the speaking class. They paid more attention on the lesson. It can be seen from their speaking score.Keywords: Role Play, Improve, Speaking Skill